(untitled) (International Journal of Engineering and Computer Science, 2014)
In modern world, the demand of network is increasing rapidly. This ever increasing usage of such network requirements also demands fast recovery from network failures. The multipath routing is one of the most promising routing schemes to accommodate the diverse requirements of the network. It has basic features like load balancing and improved bandwidth. In this paper, we have presented a review of some modern and popular methods for the reliable multi path routing. A brief introduction to the concept of multipath routing is also elaborated. The merits and demerits of each multi path routing methods are discussed.